Літературний бренд (не) змінює канон: випадок Марії Матіос» - Вардеванян, Світлана Іванівна (ЧНУ імені Юрія Федьковича, 2023)
Maria Matios belongs to the Ukrainian literary generation of the eighties of the 20th century. The writer has a lot of prose texts, the editions are fantastic for the Ukrainian book market, the affection of the mass reader is undeniable. That is, we are dealing with a literary brand. However, this literary brand, highly sought after by publishers, readers, and translators, and awarded with many awards, did not enter the literary canon. Literary criticism mostly assigns the prose works of Maria Matios a place in the so-called “mass” literature, the writer’s works are not included in the school curriculum. The prose of Maria Mathios is an interweaving of historical and femincentric themes. The historical theme in Matios’s prose is not presented from the angle usual for similar themes. The reader does not see the historical twists and turns that usually take place in the capitals, he observes the consequences of major historical events in the small village of Roztoky in Bukovyna. The village, which for the author herself is not the periphery, but the center, because she was born in it. Just as peripheral to the patriarchal masculine center is the “second sex”, on whose behalf the story is told in the writer’s texts. The women of Maria Mathios talk about their psychological and bodily experiences of survival in times of great social upheaval. The prose texts of Maria Mathios make sense of the colonial traumas of Ukrainian memory, centering the peripheral. The author uses one of the most relevant decolonial narrative strategies – the archival impulse. The writer delegitimizes the story officially broadcast by the former metropolis; emphasizes the history of national resistance. The prose of Maria Mathios is important and necessary for our literary canon
LITERARY BRAND (NOT) CHANGING THE CANON: THE CASE OF MARIA MATIOS
Keywords: Maria Matios; modern Ukrainian literature; literary canon; colonial trauma; arhival impulse in art; narrative strategies